The Biographical Approach in Andragogical Research in Adult Learning (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The following text is the author’s attempt to review biographical research conducted by Polish andragogues. The author defines this field of research using the term ‘biographical approach’ and connects it with the concept of biographicity. The text presents the development of research in the biographical approach from a temporal perspective and indicates the author’s own position within this research. It highlights the significance of the biographical approach in broadening the perspective of lifelong learning concepts. The author points out the most important achievements of Polish andragogical research in the biographical approach.